VertU: universal multilocus primer sets for eDNA metabarcoding of vertebrate diversity, evaluated by both artificial and natural cases - Wang, Zichen; Liu, Xilin; Liang, Dan; Wang, Qiaoyun; Zhang, Lu; Zhang, Peng (Frontiers in Ecology and Evolution, 2023)
Environmental DNA (eDNA) metabarcoding is a powerful tool for monitoring biodiversity in natural ecosystems. The accuracy of eDNA metabarcoding relies heavily on the PCR primers that amplify target sequences. For vertebrates, most available primers are designed for particular groups. There have been inadequate attempts to design “universal” primers applicable to all vertebrates. Here, we developed three new universal primer sets (V12S-U, V16S-U, and VCOI-U) targeting mitochondrial 12S, 16S, and COI genes, respectively. They work for all vertebrate groups, with amplification length of 200-250 bp, facilitating the use of short-read sequencing platforms. We evaluated and compared the species detection ability of our primer sets and seven previously published ones through both in-silico PCR and experiment tests with mock DNA and zoo eDNA. The species detection success of the new primer sets is over 90%, showing better performance than previously published primer sets. We also tested our new primers with water eDNA samples of natural environments, and detected a total of 895 vertebrate OTUs (BLAST identity ≥ 0.95), comprising 182 species, 195 genera, and 94 families. Our results indicated that utilizing multiple markers can achieve better species detection than using only a single marker, which is especially important for monitoring large biological communities like vertebrates. The new primer sets enable researchers to detect the presence of species of different vertebrate groups in one eDNA metabarcoding survey, which simplifies the workflow and reduces the cost. It has the potential to serve as an alternative/complementary tool for future eDNA metabarcoding studies targeting vertebrates.